Environment optimization for crowd evacuation. (29th April 2015) - Berseth, Glen; Usman, Muhammad; Haworth, Brandon; Kapadia, Mubbasir; Faloutsos, Petros
Abstract: The layout of a building, real or virtual, affects the flow patterns of its intended users. It is well established, for example, that the placement of pillars at proper locations can often facilitate pedestrian flow during the evacuation of a building. Such considerations are therefore important for architects, game level developers, and others whose domains involve agents navigating through buildings. In this paper, we take the first steps towards developing a simulation framework that can be used to study the optimal placement of architectural elements, such as pillars or doors, for the purposes of facilitating dense pedestrian flow during the evacuation of a building. In particular, we show that the steering algorithms used to model the local navigation abilities of the agents significantly affect the results, which motivates the need for a statistically valid approach and further study. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Building layout has a significant impact on the flow patterns of its intended users. We propose a simulation framework that can be used to study the optimal placement of architectural elements, such as pillars or doors, for the purposes of facilitating dense pedestrian flow during the evacuation of a building. Our findings show that the optimal environment configuration depends on the nature of the collision avoidance algorithm used, and there is no single optimal solution for different crowd densities and flow patterns.